The Intersection of Religion, Public Policy, and Women's Online Activism in Sri Lanka and Afghanistan: A Comparative Analysis - Nandy, Debasish; Besra, Ananta Kumar (FISIP UIN Sunan Gunung Djati Bandung, 2024)
Research Problem: Women’s activism through social media in South Asia, particularly in Sri Lanka and Afghanistan, is shaped by a complex interplay of religion, public policy, and socio-political contexts. While social media offers opportunities for empowerment and advocacy, its role remains contested due to societal barriers, political constraints, and religious influences. Research Purposes: This study aims to explore the dynamics of women’s online activism in Sri Lanka and Afghanistan, examining how socio-economic, political, and religious factors influence their digital engagement. It seeks to identify key challenges and highlight the comparative impact of social media on women’s advocacy in these two countries. Research Methods: The study employs a qualitative approach, using content analysis of secondary data, including reports, academic studies, and media articles. Comparative analysis is applied to evaluate the socio-political and religious factors shaping women’s digital activism in Sri Lanka and Afghanistan. Results and Discussion: In Sri Lanka, women benefit from higher literacy rates and a relatively open societal structure, enabling them to use social media effectively for addressing issues like corruption and economic mismanagement. However, ethnic and religious divisions limit cohesive activism. In Afghanistan, women demonstrate resilience by leveraging platforms like Facebook and WhatsApp despite facing severe socio-religious constraints and the Taliban’s repressive policies. The analysis underscores the critical role of social media as both a tool for advocacy and a contested space for control and suppression. Research Implications and Contributions: The study highlights the necessity of addressing structural barriers to enhance women’s digital participation. Regional collaboration, improved digital literacy, and international advocacy are recommended to amplify women’s voices in both countries. The findings contribute to the broader discourse on the intersection of religion, public policy, and digital activism, providing insights for policymakers and activists working toward inclusive social progress.